Effect of irrigation water regimes on yield of Tetragonia tetragonioides - Bekmirzaev, Gulom (2019)
The main purpose of this experiment was to study the effect of several irrigation water regimes on Tetragonia tetragonioides (Pall) O. Kuntze in semi-arid regions. During the experiment period, it was measured that several irrigation regimes were affected in terms of growth, biomass production, total yield, mineral composition, and photosynthetic pigments. The experiment was conducted in the greenhouse at the University of Algarve (Portugal). The study lasted from February to April in 2010. Three irrigation treatments were based on replenishing the 0.25-m-deep pots to field capacity when the soil water level was dropped to 70% (T1, wet treatment), 50% (T2, medium treatment), and 30% (T3, dry treatment) of the available water capacity. The obtained results showed that the leaf mineral compositions of chloride and sodium, the main responsible ions for soil salinization and alkalization in arid and semi-arid regions, enhanced with the decrease in soil water content. However, the minimum amounts of chlorophyll, carotenoids, and soluble carbohydrates in the leaf content were obtained in the medium and driest treatments. On the other hand, growth differences among the several irrigation regimes were very low, and the crop yield increased in the dry treatment compared to the medium treatment; thus, the high capacity of salt-removing species suggested an advantage of its cultivation under dry conditions.